Myocardial effective transverse relaxation time T2* Correlates with left ventricular wall thickness: A 7.0 T MRI study. Issue 6 (25th June 2016) - Huelnhagen, Till; Hezel, Fabian; Serradas Duarte, Teresa; Pohlmann, Andreas; Oezerdem, Celal; Flemming, Bert; Seeliger, Erdmann; Prothmann, Marcel; Schulz‐Menger, Jeanette; Niendorf, Thoralf
Abstract : Purpose: Myocardial effective relaxation time T 2 * is commonly regarded as a surrogate for myocardial tissue oxygenation. However, it is legitimate to assume that there are multiple factors that influence T 2 * . To this end, this study investigates the relationship between T 2 * and cardiac macromorphology given by left ventricular (LV) wall thickness and left ventricular radius, and provides interpretation of the results in the physiological context. Methods: High spatio‐temporally resolved myocardial CINE T 2 * mapping was performed in 10 healthy volunteers using a 7.0 Tesla (T) full‐body MRI system. Ventricular septal wall thickness, left ventricular inner radius, and T 2 * were analyzed. Macroscopic magnetic field changes were elucidated using cardiac phase–resolved magnetic field maps. Results: Ventricular septal T 2 * changes periodically over the cardiac cycle, increasing in systole and decreasing in diastole. Ventricular septal wall thickness and T 2 * showed a significant positive correlation, whereas the inner LV radius and T 2 * were negatively correlated. The effect of macroscopic magnetic field gradients on T 2 * can be considered minor in the ventricular septum. Conclusion: Our findings suggest that myocardial T 2 * is related to tissue blood volume fraction. Temporally resolved T 2 * mapping could be beneficial for myocardial tissue characterization and for understanding cardiac (patho)physiology in vivo. Magn Reson Med 77:2381–2389, 2017. © 2016 International Society for Magnetic Resonance in Medicine